Addressing the theoretical and experimental aspects of low-dimensional-materials-based fet immunosensors: A review - Martins, Ernane de Freitas; Pinotti, Luis Francisco; Silva, Cecilia de Carvalho Castro; Rocha, Alexandre Reily [UNESP] (MDPI, 2021)
Electrochemical immunosensors (EI) have been widely investigated in the last several years. Among them, immunosensors based on low-dimensional materials (LDM) stand out, as they could provide a substantial gain in fabricating point-of-care devices, paving the way for fast, precise, and sensitive diagnosis of numerous severe illnesses. The high surface area available in LDMs makes it possible to immobilize a high density of bioreceptors, improving the sensitivity in biorecognition events between antibodies and antigens. If on the one hand, many works present promising results in using LDMs as a sensing material in EIs, on the other hand, very few of them discuss the fundamental interactions involved at the interfaces. Understanding the fundamental Chemistry and Physics of the interactions between the surface of LDMs and the bioreceptors, and how the operating conditions and biorecognition events affect those interactions, is vital when proposing new devices. Here, we present a review of recent works on EIs, focusing on devices that use LDMs (1D and 2D) as the sensing substrate. To do so, we highlight both experimental and theoretical aspects, bringing to light the fundamental aspects of the main interactions occurring at the interfaces and the operating mechanisms in which the detections are based.
Keywords: Electrochemical; FET; Immunosensor; Low-dimensional materials